2022
DOI: 10.3390/bios12080609
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz Asymmetric S-Shaped Complementary Metasurface Biosensor for Glucose Concentration

Abstract: In this article, we present a free-standing terahertz metasurface based on asymmetric S-shaped complementary resonators under normal incidence in transmission mode configuration. Each unit cell of the metasurface consists of two arms of mirrored S-shaped slots. We investigate the frequency response at different geometrical asymmetry via modifying the dimensions of one arm of the resonator. This configuration enables the excitation of asymmetric quasi-bound states in the continuum resonance and, hence, features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 66 publications
0
1
0
Order By: Relevance
“…However, there is a significant obstacle in developing Terahertz (THz) sensors that can detect analytes with high sensitivity due to the substantial difference between the THz wavelength and analyte thickness or quantity within the tissue [58]. Al-Naib [58] addressed this obstacle by developing a Terahertz meta-surface based on s-shaped complementary resonators to investigate glucose concentration levels associated with different diabetes conditions. The research showed significant resonance frequency redshifts of 110.6 GHz and improved wavelength sensitivity compared with previous studies, making it a potential tool for detecting hypoglycemia and hyperglycemia.…”
Section: Nir/mid Absorption Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is a significant obstacle in developing Terahertz (THz) sensors that can detect analytes with high sensitivity due to the substantial difference between the THz wavelength and analyte thickness or quantity within the tissue [58]. Al-Naib [58] addressed this obstacle by developing a Terahertz meta-surface based on s-shaped complementary resonators to investigate glucose concentration levels associated with different diabetes conditions. The research showed significant resonance frequency redshifts of 110.6 GHz and improved wavelength sensitivity compared with previous studies, making it a potential tool for detecting hypoglycemia and hyperglycemia.…”
Section: Nir/mid Absorption Spectroscopymentioning
confidence: 99%
“…TES relies on the principle that glucose levels affect the body's heat distribution, which in turn affects the emitted thermal radiation (Figure 11). However, there is a significant obstacle in developing Terahertz (THz) sensors that can detect analytes with high sensitivity due to the substantial difference between the THz wavelength and analyte thickness or quantity within the tissue [58]. Al-Naib [58] addressed this obstacle by developing a Terahertz meta-surface based on s-shaped complementary resonators to investigate glucose concentration levels associated with different diabetes conditions.…”
Section: Nir/mid Absorption Spectroscopymentioning
confidence: 99%
“…For practical applications, it is difficult to change the structural parameters of waveguides, but the waveguide's refractive index may be changed much more easily than its structural properties, which makes it possible to accomplish independent tuning of the Fano resonances that are more suited for sensing [47]. The following is the definition of the sensitivity of refractive index sensing [41,48]:…”
Section: Refractive Index Sensingmentioning
confidence: 99%
“…Metasurfaces have excellent electromagnetic properties beyond the limitation of natural materials [2], which showing a variety of flexible control of parameters such as amplitude [3], phase [4,5], polarization [6], etc. Therefore, due to the application in the spectrum range from terahertz to visible light [7], such as filters [8,9], biosensors [10][11][12][13], perfect absorbing materials [14,15] * Author to whom any correspondence should be addressed. and optical switches [16,17], metasurfaces have aroused great research interest.…”
Section: Introductionmentioning
confidence: 99%